Spatial distribution of thunderstorm (short-duration) Rainfall in lower Gangetic Basin* (MAUSAM, 1970)
An attempt has been made to determine-the relationship between the rainfall recorded at a point and over the surrounding area in association with short duration thunderstorm rainfall over the lower Gangetic Basin. It is seen that in the case of short duration (6 hours or less) thunderstorm rain (i) the ratio of maximum average areal rainfall to maximum average point rainfall for an area of two thousand sq. km is about 75 per cent whereas for a larger area often thousand sq km, it is of the order of 40 per cent; (ii) the percentage ratios of average areal rainfall finds to maximum point rainfall for areas of2500, 5000 and 7500 sq. km are 40, 28 and 21 respectively; (iii) the distribution of point rainfall at different stations during thunderstorm activity can be represented in the form of an envelope curve, which will enable the probable maximum rainfall at any station to be computed knowing the maximum rainfall recorded and the distance of its occurrence ; and (iv) simultaneous thunderstorm activity with rainfall in the lower Gangetic Basin appears mostly confined to an area of about 200 km radius.